A Study of Coherence in the Writings of EFL Advanced Iraqi learners - Abid, Rana Abd Alsettar; Abdul-Ridha, Nada Salih (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2006)
Coherence has proved to be an essential component that makes a written text both effective and readable. However, it is found that incoherence is a remarkable feature in the writings of EFL Learners. In order to achieve a-more thorough understanding of this concept, its importance in writing, and the reasons behind neglecting it by EFL learners, coherence, in terms of Pilus( 1996) and Lee (2002) criteria, is to he examined in (20) descriptive texts written by EFL Iraqi (earners. The implications of the findings are to be thoroughly discussed and suggestions are provided so as to improve teaching writing skill in foreign language classroom.
Keywords: الدراسات اللغوية -- اللغات الأجنبية -- اللغة الإنجليزية -- الكتابات الإنجليزية -- العراق